Development of English Language Teaching Materials for the Economic Education Study Program - wiwit kurniawan; Saptina Retnawati (ELT-Lectura, 2019)
The purpose of this study was to produce English language teaching materials for economic education study programs with a contextual approach. This research is a research and development (R and D) which uses ADDIE development model. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were students of Economic Education in class 02 PIEE 01 consisting of 30 students. The instruments used in this study are: (1) Instruments for measuring validity, including validation sheets; (2) Instruments for measuring practicality, including observer assessment sheets, student response sheets and learning implementation observation sheets; (3) Instruments for measuring effectiveness, including motivation questionnaires and learning achievement tests. The outcome of this research was learning devices in the form of module. The validation results showed that the lesson plan and module meet valid criteria with very good category. The results of field trials showed that the lesson plan and module meet practical and effective criteria. The practicality of the learning device developed reached a very good category based on observations of the implementation of learning and observer assessment, the module reached a good category based on student responses. Effectiveness reached an effective category based on the level of motivation and completeness of student learning. The percentage of the number of students who reached the high minimum category in the motivation questionnaire was 87.57% and the percentage of achievement in classical was 75%. Thus, it can be concluded that the module is effective in terms of student learning motivation.